If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 = -5x + 3x + 9 Reorder the terms: 33 = 9 + -5x + 3x Combine like terms: -5x + 3x = -2x 33 = 9 + -2x Solving 33 = 9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 33 + 2x = 9 + -2x + 2x Combine like terms: -2x + 2x = 0 33 + 2x = 9 + 0 33 + 2x = 9 Add '-33' to each side of the equation. 33 + -33 + 2x = 9 + -33 Combine like terms: 33 + -33 = 0 0 + 2x = 9 + -33 2x = 9 + -33 Combine like terms: 9 + -33 = -24 2x = -24 Divide each side by '2'. x = -12 Simplifying x = -12
| 5x+3y=9 | | [p+2]=10 | | 5*(3-x)=4x+18 | | [x]=5 | | 10x(8+2)-2= | | 8x=5(x+3) | | 2x^2+13x+7=0 | | 6(3x+5)=5(8x+6) | | -x^2+4x=-47 | | x-3y=-12 | | x+(x+2)+(x+4)=(x+6)+8 | | 5x+3=6-3x | | .5x-.2(50+x)=.16(50) | | -(x+8)=2(4x+5) | | 3x-20=x+7 | | 41x=137 | | 18+12x=3x-9 | | x-18.22=59.67 | | 9x^4-24x^3+6x^2+24X-16=0 | | 36-3x=20+5x | | 6n-42-2n=18+2n | | -0.1(40)+.5x=.3(40+x) | | 2(3x-4)+2=6 | | 13-5x=28-2x | | 4(x-6)+5=13 | | 5x^3-34x^2-21x=0 | | (4x+10)=(5x-20) | | 2(x-15)=8x | | x+2=x+3 | | 2x-(3x+5)=x-10 | | 4w^2-16x=-15 | | -4+.5x=(12+x) |